Efektivitas Repelen Ekstrak Kulit Buah Limau Kuit (Citrus hystrix DC) terhadap Nyamuk Aedes aegypti - Zafira Aisyah Putri; Erida Wydiamala; Lia Yulia Budiarti (Homeostasis, 2022)
Abstract: Dengue Hemorrhagic Fever (DHF) is one of the important health problems caused by the Aedes aegypti mosquitoes. One method to prevent DHF is using mosquito’s repellent products, but some mosquito’s repellent products contain synthetic chemicals with high concentrations that can interfere with human’s health. Limau kuit (Citrus hystrix DC) contains flavonoids, alkaloids, and tannins that can be used as a natural repellent. This study aims to analyze the effectiveness of repellent extract of limau kuit’s peel (Citrus hystrix DC) against Aedes aegypti mosquitoes. This study used a true experimental post test only with control group design, consist of 4 concentrations from ethanol extract of limau kuit’s peel (12.5%, 25%, 50%, 100%), DEET 15% (positive control), and applied with aquadest (negative control) with 4 replications. The concentrations of ethanol extract of limau kuit’s peel would be apply to the skin of mice’s back that will be exposed by mosquitoes for 5 minutes at 0, 60, 120, and 180 minutes. The results of this study showed the repellent was effective at 100% concentrations. The results of Kruskal-Wallis tests in all minutes were obtained p<0.05 and the results of Mann-Whitney test at 0, 60, and 120 minutes were obtained p>0.05. The conclusion from this study is the ethanol extract of limau kuit’s peel has repellent activity against Aedes aegypti mosquitoes. Keywords:  Aedes aegypti, Citrus hystrix DC, limau kuit’s peel, repellent Abstrak: Demam Berdarah Dengue (DBD) adalah salah satu masalah kesehatan yang disebabkan nyamuk Aedes aegypti. Salah satu cara mencegah DBD adalah dengan menggunakan produk penolak nyamuk (repelen), tetapi sebagian produk anti nyamuk mengandung bahan kimia yang dapat mengganggu kesehatan manusia. limau kuit (Citrus hystrix DC) memiliki kandungan flavonoid, alkaloid, dan tanin yang dapat dimanfatkan sebagai repelen alami. Tujuan penelitian ini menguji efektivitas ekstrak kulit buah limau kuit (Citrus hystrix DC) sebagai repelen terhadap nyamuk Aedes aegypti. Penelitian ini bersifat true experimental post test only with control group design, terdiri dari 4 konsentrasi ekstrak etanol kulit buah limau kuit (12,5%, 25%, 50%, 100%), DEET 15% (kontrol positif), dan aquadest (kontrol negatif) dengan pengulangan 4 kali. Serial konsentrasi ekstrak etanol kulit buah limau kuit, K(+), dan K(-) dioleskan ke kulit punggung mencit yang dipaparkan nyamuk selama 5 menit pada menit ke-0, 60, 120 dan 180. Hasil penelitian menunjukkan efektivitas repelen pada konsentrasi 100%. Hasi uji Kruskal-Wallis pada semua menit didapatkan p<0,05 dan hasil uji Mann-Whitney pada menit 0, 60, dan 120 didapatkan p>0,05. Simpulan dari penelitian ini adalah ekstrak kulit buah limau kuit memiliki efektivitas repelen terhadap nyamuk Aedes aegypti. Kata-kata kunci: Aedes aegypti, Citrus hystrix DC, kulit buah limau kuit, repelen